Os marcos da paisagem da cidade no contexto da trama urbana de Natal/RN: um estudo a partir do Morro do Careca, o Midway Mall, o Pórtico dos Reis Magos e a Ponte Newton Navarro - Soares, Marília Medeiros (2012)
The present work is a study on the functions performed by landmarks landscape Natal / RN in the urban fabric, in the case of Midway Mall, the Portico dos Reis Magos, the Morro do Careca and Newton Navarro Bridge. For such goals established itself as analyze the functionality of the milestones presented here in the urban fabric; discuss the importance of these landmarks of the city landscape in the process of urbanization of Natal, and identify and spatialize actions related to the use of territories where are located landmarks, discussing their reflections. To achieve these goals we chose to use as a literature search procedures, the problematic concept, working with oral sources, and reading speechless. To support this research the main concepts were worked landscape, city, landmark, public space, circuits, among others. After going over the theory, consistent with the empirical data, it appears that the landmarks studied here have different functions and features, but all carry different forms of fascination for the public and visitors to the city, and every man your way, influence the public space, land speculation and feature importance in the process of urbanization of Natal